"A Stern Language of Beauty": Ecological Grief and Ecofeminist Ethics in Paula Meehan's Poetry. (5th April 2022) - Du, Jun
Abstract: Through publicly mourning the loss of family members, communities, and natural habitats, Paula Meehan's poems de-privatize and politicize grieving and lamentation, functioning in resistance to the existing social and cultural norms. From Reading the Sky (1985) to As If By Magic (2020), Meehan has been conscious of and has continuously delineated the deterioration of the ecosystem due to the exploitative expansion of human society. Drawing on ecofeminist theories and Judith Butler's theorizations of precariousness and grievability, the essay explores how Meehan depicts ecological grief and the interrelationship between human and nonhuman beings at different stages of her poetic career; it further probes how she illuminates and complicates the ethics of mourning and ecofeminism in her ecological elegies.